The influence of pacing during 6-minute supra-maximal cycle ergometer performance - Aisbett, B.; Le Rossignol, P.; Sparrow, W. A. (Journal of Science and Medicine in Sport, 2003)
The aim of this study was to evaluate the influence of pacing on performance, oxygen uptake (VO2), oxygen deficit and blood lactate accumulation during a 6-minute cycle ergometer test. Six recreational cyclists completed three 6-minute cycling tests using fast-start, even-pacing and slow-fast pacing conditions. Cycle ergometer performance was measured as the mean power output produced for each cycling test. Energy system contribution during each cycling trial was estimated using a modified accumulated oxygen deficit (AOD) method. Blood lactate concentration was analysed from blood sampled using a catheter in a forearm vein prior to exercise, at 2 minutes, 4 minutes and 6 minutes during exercise, and at 2 minutes, 5 minutes and 10 minutes post-exercise. There was no significant difference between the pacing conditions for mean power output (P = 0.09), peak VO2 (P = 0.92), total VO2 (P = 0.76), AOD (P = 0.91), the time-course of VO2 (P = 0.22) or blood lactate accumulation (P= 0.07). There was, however, a significant difference between the three pacing conditions in the oxygen deficit measured over time (P = 0.02). These changes in the time-course of oxygen deficit during cycling trials did not, however, significantly affect the mean power output produced by each pacing condition.